Prospects for improving food security in Kazakhstan - Gridneva Y.Е.; Kaliakparova, G.Sh.; Zhangirova, R.N.; Parmanova, R.S.; Kosherbayeva, A.B. (BUKETOV BUSINESS REVIEW, 2023)
Object: The study was based on the current state of the country’s food security.Since the research topic is relevant, hence the purpose of writing the article was to identify possible options for improving food security and develop its model in the Republic of Kazakhstan. Methods: Analysis method — an analysis of Kazakhstan food development in the field of accessibility, regulation of food prices, improving the quality of life, etc. were carried out. A statistical method by which conclusions are drawn on the past period and on the prospects for food security. The modeling method contributed to the formation of a food security model. Findings:One can say about the food security of the country when its population is stably provided with basic foodstuffs at the expense of its own production. Here it is important to focus on economic, social and environmental aspects, taking into account an integrated and systematic approach. The results of the study are derived in the proposed model of food security. Conclusions:The main scientific provisions obtained in the course of the study can be used as information and analytical material for the development and implementation of an effective policy to ensure food security in Kazakhstan. Natural and labor resources allow the state to become a self-sufficient country in the food order. The creation and activities of the council in the field of food security of the republic should resolve all the problems that currently exist.